Predictors of short-term functional recovery in ischemic stroke rehabilitation at community hospitals in Singapore - Lai, Wei Na; Tan, Cheryl Yan Fang; Ong, Chong Yau; Wong, Michelle Shu Jing; Low, Lian Leng (Frontiers in Stroke, 2025)
ObjectivesStroke remains a leading cause of death and disability worldwide. While functional outcome predictors are well established in acute rehabilitation settings, less is known in community hospitals, which typically manage stroke patients with moderate or isolated impairments. This study aimed to identify predictors of short-term functional improvement in stroke survivors admitted to community hospitals in Singapore.DesignProspective cohort study.Setting and participantsThe study included 216 stroke survivors admitted to Outram and Sengkang Community Hospitals for inpatient rehabilitation.MethodsFunctional status was measured using the Modified Barthel Index (MBI) on admission and discharge. Data on depressive symptoms (PHQ-2), resilience (CD-RISC-10), comorbidities, stroke severity (NIHSS), time to rehabilitation initiation, and sociodemographics were collected. Logistic regression identified predictors of significant functional improvement, defined as at least a one-level increase in MBI.ResultsParticipants' mean age was 71.20 years; most were male (59.30%), Chinese (82.00%), unemployed (58.80%), and living with family (86.50%). Functional improvement was more likely among those who were premorbidly independent (65.70%), had mild depressive symptoms (PHQ-2 ≤ 2; 63.70%), experienced mild strokes (NIHSS ≤ 4; 43.10%), or started rehabilitation within 1 day of onset (33.80%). Older age (p = 0.02) and shorter time to rehabilitation (p = 0.03) independently predicted functional improvement.Conclusion and implicationsOlder age and early rehabilitation were significantly associated with greater short-term functional gains in community hospital stroke survivors, underscoring the importance of timely rehabilitation to optimize recovery after stroke, even for older adults.